A study of Commercial banking and its function - Bamel, Seema (Universal Research Reports, 2017)
A commercial bank is a type of financial institution that provides services like accepting deposits, making business loans, and offering basic investment products. The term commercial bank can also refer to a bank, or a division of a large bank, which precisely deals with deposits and loan services provided to corporations or large or middle-sized enterprises as opposed to individual members of the public or small enterprises. For example, Retail banking, or Merchant banks. A commercial bank can also be defined as a financial institution that is licensed by law to accept money from different enterprises as well as individuals and lend money to them. These banks are open to the mass and assist individuals, institutions, and enterprises. Basically, a commercial bank is the type of bank people tend to use regularly. They are formulated by federal and state laws on the basis of the coordination and the services they provide.